AKULTURASI ISLAM DALAM BUDAYA LOKAL - Al-Amri, Limyah; Haramain, Muhammad (LPPM IAIN Parepare, 2017)
The subject matter raised in this paper is how acculturation of Islam and local culture in Indonesia. Using historical text studies. In this paper suggests the success of Islam that came from Arabs managed to dialogue and accepted in the local cultural landscape that has long been rooted in the archipelago. The findings are that Islam is able to understand the existing local cultural setting and internalize the cultural setting so that its existence can be accepted by the community. This success is inseparable from the cultural approach adopted by Islamic preachers of the XIII century who acculturate Islamic and local culture so that it becomes an inseparable unity.